Penerapan BMC (Business Model Canvas) Menggunakan Analisis SWOT pada UMKM Dimas Tempe - Alfina, Febi Silvia; Ramadhan, Surya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the business model of Dimas Tempe MSME using the Business Model Canvas (BMC) and SWOT analysis approaches. Data were collected through interviews, observations, and document analysis. The BMC helped map key business elements such as customer segments, value propositions, and cost structure. SWOT analysis revealed strengths like product quality and customer loyalty, and weaknesses such as limited digital marketing and personal funding. Opportunities aries from the healthy food trend and e-commerce potential, while threats include market competition and raw material price fluctuations. The integration of BMC and SWOT provides a comprehensive view, enabling the MSME to develop strategies that leverage strengths, address weaknesses, and anticipate threats. This approach proves effective in supporting sustainable and adaptive business development.